Isoniazid Microencapsulation With HPMCP HP-50 and HPMCP HP- 55 (2:3) Coating Using Solvent Evaporation Method - Hestiary Ratih; Gladdis Kamilah Pratiwi; Fikri Alatas; Mia Agustin; Bella Dewinta Saraswati (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
The combination formulation of tuberculosis drugs may cause interactions if these drugs are givensimultaneously. Rifampin (RIF) decomposes in the stomach when given concurrently with isoniazid(INH), which results in a decrease in the bioavailability of RIF. The purpose of this study is to makeINH microcapsules using HPMCP HP-50 and HP-55 coatings to prevent these interactions. Theprocess of making INH: HPMCP HP-50 and HP-55 (2:3) microcapsules was done by using solventevaporation method. The entrapment efficiency of INH: HPMCP HP-50 and HP-55 (2:3) were 83.21%and 91.57%, respectively. The dissolution test of INH: HPMCP HP-50 and HP-55 microcapsules metthe requirements of the Indonesian Pharmacopoeia Edition V. The FTIR results showed that there wasno change either in the chemical composition of isoniazid or in the coating of the microencapsulation.Scanning Electron Microscopy (SEM) showed the active substance was well coated. This studyproduces microcapsules that can provide a delayed release effect, so it is expected that INH: HPMCPHP-50 and HP-55 (2:3) microcapsules can be released in the intestines without interacting with RIF.Keywords: HPMCP HP 50, HPMCP HP-55, isoniazid, microcapsules, solvent evaporation method